Automated calibration of model-driven reconstructions in atom probe tomography - Fletcher, C; Moody, MP; Fleischmann, C; Dialameh, M; Porret, C; Geiser, B; Haley, D (IOP Publishing, 2022)
Traditional reconstruction protocols in atom probe tomography frequently feature image distortions for multiphase materials, due to inaccurate geometric assumptions regarding specimen evolution. In this work, the authors' outline a new reconstruction protocol capable of correcting for many of these distortions. This new method uses predictions from a previously developed physical model for specimen field evaporation. The application of this new model-driven approach to both an experimental semiconductor multilayer system and a fin field-effect transistor device (finFET) is considered. In both systems, a significant reduction in multiphase image distortions when using this new algorithm is clearly demonstrated. By being able to quantitatively compare model predictions with experiment, such a method could also be applied to testing and validating new developments in field evaporation theory.